2019
DOI: 10.1002/csr.1724
|View full text |Cite
|
Sign up to set email alerts
|

Impact of disclosure and assurance quality of corporate sustainability reports on access to finance

Abstract: This paper investigates the impact of corporate social responsibility (CSR) disclosure quantity, quality, and external validation concerning assurance on capital constraints.We examine if these disclosure characteristics matter to the investors in the financial market, then they should be positively evaluated by financial market participants.More specifically, we study the effects of disclosure quantity, quality, and assurance on the access to financial resources for reporting firms. Analysis of data of an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
107
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(138 citation statements)
references
References 81 publications
(175 reference statements)
8
107
0
4
Order By: Relevance
“…Pflugrath et al () and Hodge et al () state that assured sustainability reports are perceived with a higher reliability than without assurance. Several studies establishing econometric models based on multivariate analysis support these findings (Cuadrado‐Ballesteros, Martínez‐Ferrero, & García‐Sánchez, ; Martínez‐Ferrero & García‐Sánchez, ; García‐Sánchez, Hussain, Martínez‐Ferrero, & Ruiz‐Barbadillo, ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 82%
See 1 more Smart Citation
“…Pflugrath et al () and Hodge et al () state that assured sustainability reports are perceived with a higher reliability than without assurance. Several studies establishing econometric models based on multivariate analysis support these findings (Cuadrado‐Ballesteros, Martínez‐Ferrero, & García‐Sánchez, ; Martínez‐Ferrero & García‐Sánchez, ; García‐Sánchez, Hussain, Martínez‐Ferrero, & Ruiz‐Barbadillo, ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 82%
“…Furthermore, O'Dwyer () examines the difficulties in creating a new assurance practice and sees a competition between the types of assurance providers: those with accounting and “non‐accounting” backgrounds. Several studies analyze the impact of the assurance providers on the credibility of ESG reports and state assurance provided by a professional accountant as more credible (Cuadrado‐Ballesteros et al, ; García‐Sánchez, Hussain, et al, ; Martínez‐Ferrero & García‐Sánchez, ; Simnett, Vanstraelen, & Chua, ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…In summary, as a consequence of the important role that institutional pressures have in information disclosure policies (i.e., García‐Sánchez, et al, , ), we believe that the structural dimensions of impression management techniques differ between sectors of activity due to the mimetic isomorphism effect (Amor‐Esteban et al, , ) and between periods of time due to legal changes in Spain that have regulated these informative practices as mandatory, favouring the normalisation of information (coercive effect).…”
Section: Institutional Pressures Effectsmentioning
confidence: 96%
“…In this sense, companies would benefit from the advantages traditionally associated with increasing organisational transparency and its impact on the reduction of asymmetric information problems and valuation of future risks (Martínez‐Ferrero, Ruiz‐Cano, & García‐Sánchez, ). Benefits include those of an economic nature associated with access to better sources of financing and with better conditions (i.e., Dhaliwal, Li, Tsang, & Yang, ; García‐Sánchez, Hussain, Martínez‐Ferrero, & Ruiz‐Barbadillo, ), as well as others of an intangible nature linked to image and business reputation (Cormier, Magnan, & Van Velthoven, ; Amran, Periasamy, & Zulkafli, ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in the investors' perspectives, CSR activities have been investigated in their relationship with financial performance [10] and access to finance [11]. CSR reports have also been put in relationships with stakeholder engagement and forecast accuracy by financial analysts: García-Sánchez et al [12] found evidence about how the joint use of global reporting initiative (GRI) guidelines, and the International Finance Corporation (IFC) performance standards (defined as GRI-IFC disclosure strategy) has a positive impact on the accuracy of analysts' forecasts.…”
Section: Introductionmentioning
confidence: 99%